On dimension of attractors of reaction-diffusion equations with periodic right-hand side - Balibrea, Francisco; Valero, José (Annales Mathematicae Silesianae, 1999)
In this paper we study the finite-dimensionality of the global attractor of a discrete dynamical system generated by a reaction-diffusion equation with non-differentiable nonlinear term and periodic right-hand side. The existence of an exponential attractor is also proved. Explicit estimates of the fractal dimension are given.